Mixed Joint Universality for L-Functions from Selberg’s Class and Periodic Hurwitz Zeta-Functions - Jasas, Mindaugas; Macaitienė, Renata (Jaunųjų mokslininkų darbai, 2020)
The so-called mixed joint universality was initiated by H. Mishou who in 2007 obtained the joint universality for the Riemann and Hurwitz zeta functions. In a wide sense, the mixed joint universality is understood as a joint universality for zeta and L-functions having and having no Euler product. In the paper, the investigation on the universality question for the collections of some zeta and L-functions is continued. More precisely, a new result on mixed joint universality property for L-functions from the Selberg class (functions defined by Dirichlet series and satisfying certain specific hypotheses (including the Euler product)) and periodic Hurwitz zeta functions (that have no Euler product) is given. The result of mixed universality can be used to prove a functional independence properties of these functions. The paper has been prepared on the basis of M. Jasas’ Master Thesis [4].